Tipologi Segregasi Permukiman Berdasarkan Faktor dan Pola Permukiman di Solo Baru, Sukoharjo - Wulangsari, Amalia (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Population growthrate has been an alternative to the new development to make a change in the physical, social and economic in peri urban areas. Development in peri urban has beenresulted in the decreasing of agricultural land productivity. In addition, inclusion of migrants have brought diversity of cultures, lifestyles and raised a dichotomy between the local population and migrants in peri urban areas. Solo Baruwas chosen as a case study of residential area in the southern part of the Surakarta. The population of Solo Baru has been rapidly increase. This kind of segregation has been become a negative impact of the development towards the peri urban are especially in social characteristic like a gap between the planned settlement and unplanned settlement. The research utilities a quantitative approach. Method of this study using a index dissimilarity and discriminan analyze. There are 4 models of segregation occurs in Solo Baru that is segregation of separated by access roads and road class, land use area, public space, and the type of home as the results of this study.The fourth model of segregation are more influenced by the determinants of segregation has been seen from variable income, occupation and education level of the population.The three selected variablesÂ represents a economic and social aspects at the Solo Baru residential.